Chronic Hepatitis Virus Infection Are Associated With High Risk of Gastric Cancer: A Systematic Review and Cumulative Analysis - Yang, Yusha; Jiang, Zufu; Wu, Weizhou; Ruan, Libin; Yu, Chengyang; Xi, Yuning; Wang, Liling; Wang, Kunpeng; Mo, Jinggang; Zhao, Shankun (Frontiers in Oncology, 2021)
Mounting studies demonstrated both chronic hepatitis B virus (HBV) and chronic hepatitis C virus (HCV) infection might be associated not only with an increased risk of hepatocellular carcinoma but also extrahepatic malignancies, i.e., gastric cancer (GC). However, a quantitative result addressing the association between HBV/HCV infection and GC development is scarce. A systematic searching to identify the eligible studies was performed in the four databases, including MEDLINE, EMBASE, Cochrane Library, and the PsychINFO. The relationship between HBV/HCV infection and the risk of GC was quantified by calculating the hazard ratio (HR) with a 95% confidence interval (CI). More methodologies of this study were available in the PROSPERO (ID: CRD42021243719). Thirteen included studies involving 7,027,546 individuals (mean age: 42.6-71.9 years) were enrolled in the pooled analyses. Two articles provided the clinical data of both HBV and HCV infection. The proportion of high methodological quality studies was 76.9% (10/13). Synthetic results from 10 eligible studies of HBV showed that HBV infection was associated with a significantly higher risk of GC when compared to the healthy controls without HBV infection (pooled HR= 1.26, 95%CI: 1.08 to 1.47, P=0.003; heterogeneity: I2= 89.3%, P< 0.001). In line with this finding, the combined effect derived from 5 included studies of HCV also supported a significant positive association between chronic HBV infection and GC development (pooled HR = 1.88, 95%CI: 1.28-2.76, P = 0.001; heterogeneity: I2 = 74.7%, P = 0.003). In conclusion, both chronic HBV and HCV infection were related to a high risk of GC. The plausible mechanisms underlying such association might be correlated to HBV/HCV infection-induced persistent inflammation, immune dysfunction, and cirrhosis.